Usefulness of left ventricular mass change to predict progression of renal dysfunction in Hispanics. Issue 1 (2nd January 2018) - Said, Sarmad; Teleb, Mohamed; Albaghdadi, Aymen Omar; Kanu, Obiajulu; Wardi, Miraie; Ngamdu, Kyari Sumayin; Sroush, Lutf Rahman; Michael, Majd; Asatrian, Asmik; Salman, Riyadh Salih; Mukherjee, Debabrata
ABSTRACT: There is a strong relation between metabolic syndrome (MetS) and left ventricular (LV) mass in Hispanic patients. This population also tends to have a higher incidence of kidney disease, with progression to dialysis. We analyzed the change in LV mass in 982 Hispanic patients with MetS and used these data to anticipate the progression of renal dysfunction. Glomerular filtration rate (GFR) was calculated using the formula described by the Chronic Kidney Disease Epidemiology Collaboration. Echocardiographic data were collected using 2-dimensionally guided M-mode echocardiography measures. The data collected were then analyzed using linear regression analyses. Results showed a lower average GFR in individuals classified as having a severe change in LV mass in comparison to those with milder change in LV mass ( P < 0.0001). This relation was also demonstrated when those with severe change in LV mass were compared with the control group ( P < 0.0001). In those ≥54 years old, the presence of MetS and LV mass were negatively correlated with GFR (regression coefficient [RC] = 14.76, P < 0.063; RC = 0.11, P < 0.0001 respectively). In patients <54 years old, no statistically significant association between the presence of MetS and GFR was seen. However, LV mass was once again negatively correlated with GFR (RC = 0.15, P < 0.0001). In conclusion, results demonstrated the association between the MetS, change in LV mass, and chronic kidney disease progression.